2011
DOI: 10.1128/jvi.05008-11
|View full text |Cite
|
Sign up to set email alerts
|

Productive Dengue Virus Infection of Human Endothelial Cells Is Directed by Heparan Sulfate-Containing Proteoglycan Receptors

Abstract: Dengue virus causes leakage of the vascular endothelium, resulting in dengue hemorrhagic fever and dengue shock syndrome. The endothelial cell lining of the vasculature regulates capillary permeability and is altered by immune and chemokine responses which affect fluid barrier functions of the endothelium. Our findings indicate that human endothelial cells are highly susceptible to infection by dengue virus (type 4). We found that dengue virus productively infects ϳ80% of primary human endothelial cells, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 81 publications
(108 reference statements)
2
102
1
Order By: Relevance
“…21 In addition to the effect of inflammatory cytokines, other mechanisms may also be involved, including direct interaction of dengue virus with endothelial cells, release of mast cell products, and pro-coagulant factors such as thrombin. [21][22][23][24][25] No definite conclusion on a causal relationship of Ang-1 and Ang-2 levels and plasma leakage could be made in this observational study. Similar trends in Ang-1 and Ang-2 levels have been found in severe malaria and sepsis, 26,27 but in contrast to DHF/DSS and sepsis, plasma leakage is not a prominent feature of malaria.…”
Section: Discussionmentioning
confidence: 90%
“…21 In addition to the effect of inflammatory cytokines, other mechanisms may also be involved, including direct interaction of dengue virus with endothelial cells, release of mast cell products, and pro-coagulant factors such as thrombin. [21][22][23][24][25] No definite conclusion on a causal relationship of Ang-1 and Ang-2 levels and plasma leakage could be made in this observational study. Similar trends in Ang-1 and Ang-2 levels have been found in severe malaria and sepsis, 26,27 but in contrast to DHF/DSS and sepsis, plasma leakage is not a prominent feature of malaria.…”
Section: Discussionmentioning
confidence: 90%
“…Recent 17 studies have shown that heparin inhibits DENV infection of HUVEC and that by 24h pi, the majority 18 of HUVEC can become DENV-antigen positive (Dalrymple and Mackow 2011). To assess this in 19 freshly isolated primary HUVEC, we cultured these cells in the presence or absence of heparin, 20 DENV-infected and measured infectious virus release by plaque assay.…”
mentioning
confidence: 99%
“…During infection, the virus first attaches to cell surface receptors, such as DC-SIGN (14), heparan sulfate (15,16), and others. After clathrin-mediated endocytosis, the low pH in the endosome induces the E proteins on the virus surface to undergo structural rearrangement from dimers to trimers (9).…”
mentioning
confidence: 99%